2018
DOI: 10.1051/0004-6361/201732081
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Hα and dust reverberation mapping of 3C 120: Testing the bowl-shaped torus geometry

Abstract: We monitored the Seyfert-1 galaxy 3C 120 between September 2014 and March 2015 at the Universitätssternwarte Bochum near Cerro Armazones in BVRI JK and a narrowband filter covering the redshifted Hα line. In addition we obtained a single contemporary spectrum with the spectrograph FAST at Mt. Hopkins. Compared to earlier epochs 3C 120 is about a factor of three brighter, allowing us to study the shape of the broad line region (BLR) and the dust torus in a high luminosity phase. The analysis of the light curves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…Furthermore, the vertical BRL structure is consistent with the bowlshaped geometry proposed by Goad et al (2012), e.g. tested by Ramolla et al (2018) for 3C 120. The 2D velocity maps of the Balmer line profiles reveal a faster response of the line wings (0−10 d) in comparison to a slower response of the line centers (10 − 30 d).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the vertical BRL structure is consistent with the bowlshaped geometry proposed by Goad et al (2012), e.g. tested by Ramolla et al (2018) for 3C 120. The 2D velocity maps of the Balmer line profiles reveal a faster response of the line wings (0−10 d) in comparison to a slower response of the line centers (10 − 30 d).…”
Section: Discussionsupporting
confidence: 86%
“…Clavel et al 1991;Hu et al 2008;Zhu et al 2009;Kawaguchi & Mori 2010;Gandhi et al 2015), which could itself be dynamic and outflowing (Chan & Krolik 2016;Williamson et al 2019;Leftley et al 2019). This class of models can also have some beneficial reverberation characteristics if they have 'bowl-shaped' geometries (Goad et al 2012;Ramolla et al 2018). Many of the general principles we have discussed would apply to such models and further detailed simulations are worthwhile.…”
Section: Limitations and Caveatsmentioning
confidence: 99%
“…The BLR reverberation mapping observations for local Seyfert galaxies and some high redshift quasars have been carried out by several groups (e.g., Peterson et al 1998Peterson et al , 2004Kaspi et al 2000;Bentz et al 2009b;Denney et al 2010;Grier et al 2012;Du et al 2014;Fausnaugh et al 2017); a compilation of ∼ 40 AGNs with secure Hβ BLR lag detection can be found in Bentz & Katz (2015) (see also Bentz et al 2009aBentz et al , 2013. Dust reverberation mapping observations have also been measured for several AGNs (Clavel et al 1989;Glass 1992;Sitko et al 1993;Glass 2004;Suganuma et al 2006;Koshida et al 2014;Pozo Nuñez et al 2014Schnülle et al 2015;Lira et al 2015;Vazquez et al 2015;Mandal et al 2018;Ramolla et al 2018;Landt et al 2019). The first systematic investigation of dust reverberation mapping was carried out by the Multicolour Active Galactic Nuclei Monitoring (MAGNUM) project (Yoshii 2002;Yoshii et al 2003;Minezaki et al 2004;Tomita et al 2006;Suganuma et al 2006;Koshida et al 2009;Sakata et al 2010;Koshida et al 2014;Yoshii et al 2014).…”
Section: Introductionmentioning
confidence: 99%